Physiotherapie, Ergotherapie und physikalische Verfahren beim Fibromyalgiesyndrom: aktualisierte Leitlinie 2017 und Übersicht von systematischen Übersichtsarbeiten - Winkelmann, Andreas; Schiltenwolf, Marcus (Der Schmerz, 2017)
BackgroundThe regular update of the guidelines on fibromyalgia syndrome, AWMF number 145/004, was scheduled for April 2017.MethodsThe guidelines were developed by 13 scientific societies and 2 patient self-help organizations coordinated by the German Pain Society. Working groups (n =8) with a total of 42 members were formed balanced with respect to gender, medical expertise, position in the medical or scientific hierarchy and potential conflicts of interest. A literature search for systematic reviews of randomized, controlled trials on physiotherapy, occupational therapy and physical therapy from December 2010 to May 2016 was performed in the Cochrane library, MEDLINE, PsycINFO and Scopus databases. Levels of evidence were assigned according to the classification system of the Oxford Centre for Evidence-Based Medicine version 2009. The strength of recommendations was achieved by multiple step formalized procedures to reach a consensus. Efficacy, risks, patient preferences and applicability of available therapies were weighed up against each other. The guidelines were reviewed and approved by the board of directors of the societies engaged in the development of the guidelines.Results and conclusionLow to moderate intensity endurance and strength training are strongly recommended. Chiropractic, laser therapy, magnetic field therapy, massage and transcranial magnetic stimulation are not recommended.
First online: 10 May 2017
Gesehen am 25.06.2018